Investigating the Effectiveness of an Inquiry-Based Intervention on Human Reproduction in Relation to Students' Gender, Prior Knowledge and Motivation for Learning in Biology. Issue 3 (2nd July 2016) - Hadjichambis, Andreas Ch.; Georgiou, Yiannis; Paraskeva-Hadjichambi, Demetra; Kyza, Eleni A.; Mappouras, Demetrios
Abstract : Despite the importance of understanding how the human reproductive system works, adolescents worldwide exhibit weak conceptual understanding, which leads to serious risks, such as unwanted pregnancies and sexually transmitted diseases. Studies focusing on the development and evaluation of inquiry-based learning interventions, promoting the knowledge of human reproduction, are very few. The purpose of this study was to evaluate the effectiveness of an inquiry-based intervention on human reproduction in relation to students' gender, prior knowledge and motivation for learning in biology. Data collection methods included students' pre- and post-tests, evaluating students' conceptual understanding regarding human reproduction, and measurements of students' motivation employing the Motivational Learning Environment survey. The sample for the pre- and post-test conceptual understanding data included the whole population of the 7th graders in Cyprus ( n  = 6465). Students' motivation data were collected from a representative sample of the entire 7th graders population ( n  = 946 students). Statistical analyses indicated a statistically significant increase in students' conceptual understanding as well as in their motivation for learning in biology. However, students' gender, prior knowledge and initial motivation for learning in biology seemed to mediate the effectiveness of the inquiry-based intervention. All of these variables are deemed, therefore, as of great importance for the design, implementation and evaluation of biology teaching interventions.